Generic one-loop matching conditions for rare meson decays - Fady Bishara; Joachim Brod; Martin Gorbahn; Ulserik Moldanazarova (Journal of High Energy Physics, 2021)
Abstract Leptonic and semileptonic meson decays that proceed via flavour-changing neutral currents provide excellent probes of physics of the standard model and beyond. We present explicit results for the Wilson coefficients of the weak effective Lagrangian for these decays in any perturbative model in which these processes proceed via one-loop contributions. We explicitly show that our results are finite and gauge independent, and provide Mathematica code that implements our results in an easily usable form.